2017
DOI: 10.1177/1457496917748228
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Clinical Pathway With Early Oral Intake and Discharge for Laparoscopic Gastrectomy

Abstract: A high completion rate of a clinical pathway with early oral intake and discharge setting for laparoscopic distal gastrectomy was achievable with an acceptably low re-admission rate. Laparoscopic distal gastrectomy is recommended as a first step for a clinical pathway with an early oral intake and discharge protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Based the original work of Kehlet and Wilmore [6], the ERAS protocol has been widely accepted and applied in the clinic. Our center have finished a trial to probe the application of ERAS in These authors contributed equally: Dan Liu, Xinxin Jing perioperative gastrectomy [7] and we found that early intake of liquid and food after surgery can facilitate postoperative restoration without increasing the incidence of fistulas, consistent with other studies [8][9][10][11]. However, it is controversial what kind of food or liquid should be the standard of early intake.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based the original work of Kehlet and Wilmore [6], the ERAS protocol has been widely accepted and applied in the clinic. Our center have finished a trial to probe the application of ERAS in These authors contributed equally: Dan Liu, Xinxin Jing perioperative gastrectomy [7] and we found that early intake of liquid and food after surgery can facilitate postoperative restoration without increasing the incidence of fistulas, consistent with other studies [8][9][10][11]. However, it is controversial what kind of food or liquid should be the standard of early intake.…”
Section: Introductionsupporting
confidence: 84%
“…Randomization was performed using PASS 11.0 software to generate random numbers and divide patients into two group evenly, using opaque sealed sequentially numbered envelopes that were opened at the moment of surgery completion. Previous our studies on postoperative ileus after gastrectomy showed a mean time to the first bowel movement of 110 ± 25.7 h (mean ± standard deviation) for control patients [8]. To detect a clinically relevant absolute difference of 24 h in time to the first bowel movement with a two-sided significance level of 0•05 and a power of 90%, it was calculated that 26 patients per study arm would be required.…”
Section: Sample Size Randomization and Statisticsmentioning
confidence: 99%
“…Our study assessed concurrent morbidities using ASA score, which is believed to affect recovery from abdominal surgery. In a clinical pathway program for gastrectomy, Nakagawa and colleagues reported ASA and postoperative morbidity were the risk factors for discharge variance [ 17 ]. Since ASA scores were significantly different between groups in our data, we performed the PSM process to reduce bias.…”
Section: Discussionmentioning
confidence: 99%